Distributed secondary control of islanded AC microgrids considering topology switching and plug-and-play operation. Issue 1 (2022) - Ganguly, Arijit; Bhadra, Shantanu; Bhowmick, Parijat; Sen, Sawan
Abstract: This paper proposes a distributed cooperative secondary voltage and frequency control scheme of a DG based islanded AC microgrid subjected to change in the topology of the microgrid communication network. The proposed control algorithm has been extended to take care of microgrid voltage and frequency profile in case of loss of communication of any DG in the network which facilitates plug-and-play operation of DGs. The centralized control schemes of an islanded microgrid pose multiple challenges in the case of maintaining microgrid voltage and frequency profile during fixed communication topology. The distributed controller gain in the proposed algorithm has been calculated using the linear quadratic regulator (LQR) principle. The adaptivity of the controller has also been introduced to consider the coupling gain dynamics among the DGs. An exhaustive Matlab simulation validates the effectiveness of the proposed distributed adaptive control design of the microgrid.